Responder
For the first problem, \( n = \frac{1}{17} \) or \( n = 51 \).
For the second problem, \( x = \log_{\frac{2}{3}}(29) - 6\log_{\frac{2}{3}}(3) - 1 \).
Solución
It seems that the equations provided involve summations that cannot be directly solved using the tools available. Let's break down each equation step by step to find a solution.
### Problem 1:
\[
\sum_{k=2}^{n}(5-2k) = \frac{-800n}{17}
\]
**Step 1: Calculate the summation.**
The summation can be simplified as follows:
\[
\sum_{k=2}^{n}(5-2k) = \sum_{k=2}^{n}5 - \sum_{k=2}^{n}2k
\]
Calculating each part:
1. The first part:
\[
\sum_{k=2}^{n}5 = 5(n-1) \quad \text{(since there are } n-1 \text{ terms)}
\]
2. The second part:
\[
\sum_{k=2}^{n}2k = 2\sum_{k=2}^{n}k = 2\left(\frac{n(n+1)}{2} - 1\right) = n(n+1) - 2
\]
Putting it all together:
\[
\sum_{k=2}^{n}(5-2k) = 5(n-1) - (n(n+1) - 2) = 5n - 5 - n^2 - n + 2 = -n^2 + 4n - 3
\]
**Step 2: Set the equation.**
\[
-n^2 + 4n - 3 = \frac{-800n}{17}
\]
**Step 3: Clear the fraction by multiplying through by 17.**
\[
-17n^2 + 68n - 51 = -800n
\]
\[
-17n^2 + 868n - 51 = 0
\]
**Step 4: Solve the quadratic equation.**
Now we can use the quadratic formula:
\[
n = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}
\]
where \( a = -17, b = 868, c = -51 \).
### Problem 2:
\[
\sum_{k=0}^{x} 108\left(\frac{2}{3}\right)^{k} = \frac{25200}{81}
\]
**Step 1: Recognize the summation as a geometric series.**
The sum of a geometric series can be calculated using the formula:
\[
S_n = a \frac{1 - r^{n+1}}{1 - r}
\]
where \( a = 108 \), \( r = \frac{2}{3} \), and \( n = x \).
**Step 2: Set the equation.**
\[
108 \frac{1 - \left(\frac{2}{3}\right)^{x+1}}{1 - \frac{2}{3}} = \frac{25200}{81}
\]
This simplifies to:
\[
108 \cdot 3(1 - \left(\frac{2}{3}\right)^{x+1}) = \frac{25200}{81}
\]
\[
324(1 - \left(\frac{2}{3}\right)^{x+1}) = \frac{25200}{81}
\]
**Step 3: Solve for \( x \).**
Now we can isolate \( x \) and solve.
Let's calculate the quadratic equation for the first problem and the geometric series for the second problem.
Solve the quadratic equation by following steps:
- step0: Solve by factoring:
\(-17n^{2}+868n-51=0\)
- step1: Factor the expression:
\(\left(-n+51\right)\left(17n-1\right)=0\)
- step2: Separate into possible cases:
\(\begin{align}&-n+51=0\\&17n-1=0\end{align}\)
- step3: Solve the equation:
\(\begin{align}&n=51\\&n=\frac{1}{17}\end{align}\)
- step4: Rewrite:
\(n_{1}=\frac{1}{17},n_{2}=51\)
Solve the equation \( 324(1 - (\frac{2}{3})^{x+1}) = \frac{25200}{81} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(324\left(1-\left(\frac{2}{3}\right)^{x+1}\right)=\frac{25200}{81}\)
- step1: Multiply the terms:
\(324-324\left(\frac{2}{3}\right)^{x+1}=\frac{2800}{9}\)
- step2: Move the expression to the left side:
\(324-324\left(\frac{2}{3}\right)^{x+1}-\frac{2800}{9}=0\)
- step3: Subtract the numbers:
\(\frac{116}{9}-324\left(\frac{2}{3}\right)^{x+1}=0\)
- step4: Rewrite the expression:
\(-324\left(\frac{2}{3}\right)^{x+1}=-\frac{116}{9}\)
- step5: Change the sign:
\(324\left(\frac{2}{3}\right)^{x+1}=\frac{116}{9}\)
- step6: Multiply by the reciprocal:
\(324\left(\frac{2}{3}\right)^{x+1}\times \frac{1}{324}=\frac{116}{9}\times \frac{1}{324}\)
- step7: Multiply:
\(\left(\frac{2}{3}\right)^{x+1}=\frac{29}{729}\)
- step8: Take the logarithm of both sides:
\(\log_{\frac{2}{3}}{\left(\left(\frac{2}{3}\right)^{x+1}\right)}=\log_{\frac{2}{3}}{\left(\frac{29}{729}\right)}\)
- step9: Evaluate the logarithm:
\(x+1=\log_{\frac{2}{3}}{\left(\frac{29}{729}\right)}\)
- step10: Move the constant to the right side:
\(x=\log_{\frac{2}{3}}{\left(\frac{29}{729}\right)}-1\)
- step11: Simplify:
\(x=\log_{\frac{2}{3}}{\left(29\right)}-6\log_{\frac{2}{3}}{\left(3\right)}-1\)
### Solutions
#### Problem 1:
The equation we derived was:
\[
-17n^2 + 868n - 51 = 0
\]
The solutions for \( n \) are:
\[
n_1 = \frac{1}{17}, \quad n_2 = 51
\]
#### Problem 2:
The equation we derived was:
\[
324(1 - (\\frac{2}{3})^{x+1}) = \\frac{25200}{81}
\]
The solution for \( x \) is:
\[
x = \log_{\\frac{2}{3}}{(29)} - 6\log_{\\frac{2}{3}}{(3)} - 1
\]
### Summary of Results:
1. For the first problem, the values of \( n \) are \( \frac{1}{17} \) and \( 51 \).
2. For the second problem, \( x \) is expressed in logarithmic form as \( \log_{\\frac{2}{3}}{(29)} - 6\log_{\\frac{2}{3}}{(3)} - 1 \).
If you need further simplification or numerical evaluation of \( x \), please let me know!
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución